Tramway Dwell Time Estimation and Analysis by Using Multiple Linear Regression Method (European Journal of Engineering Science and Technology, 2019)
Dwell time is a significant issue to designate the accurate arrival time and scheduling public transportation system in cities. In the literature, dwell time of the bus or light rail transit was studied, but studies focusing on Tramway dwell time are rare. Tramway is one of the most common public transportation systems around the world. In this paper, the Tramway dwell time is modeled by using multiple linear regression analysis. The data are collected from the kabata? ba?c?lar tramway in Istanbul-Turkey. The line covers a lot of touristic allocations and important locations in the city and generally the passenger demand is very high. The number of observations from eleven stations of this line is 171. Two separate models for weekdays and weekends include wagon occupancy, platform occupancy, the number of people who are alighting and boarding, time spent by the driver and peak hours and off-peak hours on weekdays and on weekends. The results show that between the dummy variables, the platform occupancy at the high level has more influence on tramway dwell time than wagon occupancy at a high level on weekdays, but it is vice versa on weekends. Between continuous variables, in both weekdays and weekends models, the time spent by the driver has the most impact on tramway dwell time. The number of passengers who are alighting on weekdays and the number of passengers who are boarding on the weekends have the least effect on the tramway dwell time. In this study, by considering the results, there are some significant policies suggested for policymakers to reduce the dwell time of tramway.